THE RELATIONSHIP BETWEEN SELF-REGULATED LEARNING AND STUDENT’S MATHEMATICS ACHIEVEMENT - Apriliani, Feni; Rahman Munandar, Dadang (Universitas Muhammadiyah Metro, 2026)
Mathematics learning achievement reflects students’ ability to understand and apply concepts; however, in reality, many students have not yet reached optimal results. This condition emphasizes the importance of considering internal factors that influence academic performance, one of which is self-regulated learning (SRL), defined as students’ ability to plan, monitor, and evaluate their learning process independently. This study aims to examine the relationship between SRL and students’ mathematics learning achievement. The method used is quantitative with an ex-post facto design. The population consisted of all seventh-grade students of SMPN 4 Klari in the 2024/2025 academic year, with a sample of 87 students selected using simple random sampling. The research instruments were an SRL scale and mathematics midterm exam scores, while data analysis was conducted using Spearman’s rank correlation test. The results showed a correlation coefficient (rs) of 0.308 with a significance level of 0.004 , indicating a significant positive (direct) relationship between SRL and mathematics learning achievement with a weak correlation. The results demonstrate that the higher the students’ SRL, the better their mathematics learning achievement. Prestasi belajar matematika mencerminkan kemampuan siswa dalam memahami dan menerapkan konsep, namun kenyataannya masih banyak siswa yang belum mencapai hasil optimal. Kondisi ini menegaskan pentingnya memperhatikan faktor internal yang memengaruhi capaian akademik, salah satunya adalah self-regulated learning (SRL), yaitu kemampuan siswa dalam merencanakan, memantau, dan mengevaluasi proses belajar secara mandiri. Penelitian ini bertujuan untuk mengkaji hubungan antara SRL dan prestasi belajar matematika siswa. Metode yang digunakan adalah kuantitatif dengan desain ex-post facto. Populasi penelitian mencakup seluruh siswa kelas VII SMPN 4 Klari Tahun Ajaran 2024/2025, dengan sampel sebanyak 87 siswa yang dipilih melalui teknik simple random sampling. Instrumen penelitian berupa skala SRL dan nilai UTS matematika, sedangkan analisis data dilakukan menggunakan uji korelasi rank Spearman rho. Hasil penelitian menunjukkan koefisien korelasi (rs) sebesar 0,308 dengan taraf signifikansi 0,004 , yang menunjukkan adanya hubungan positif (searah) yang signifikan antara SRL dan prestasi belajar matematika dengan tingkat hubungan yang lemah. Hasil penelitian menunjukkan bahwa semakin tinggi tingkat SRL siswa, maka semakin baik prestasi belajar matematika yang dicapai.